Corrosion inhibition of brass 60Cu–40Zn in 3% NaCl solution by 3-amino-1, 2, 4-triazole-5-thiol. Issue 6 (June 2020) - Damej, M.; Chebabe, D.; Abbout, S.; Erramli, H.; Oubair, A.; Hajjaji, N.
Abstract: In this article, we tested a new organic molecule used as a corrosion inhibitor of the 60Cu–40Zn alloy in an aqueous solution similar to sea water 3% NaCl namely 3-amino-1, 2, 4-triazole-5-thiol (ATT) using stationary and transient electrochemical methods (polarization curves and electrochemical impedance spectroscopy (EIS)). In addition, the metal surface analysis was performed by the scanning electron microscopy (SEM) coupled with the X-ray dispersion energy (EDX) in the absence and in the presence of the inhibitor tested. Analysis of the polarization curves reveals that the ATT acts as a mixed inhibitor, while the inhibition efficiency reaches a value of 97% for a concentration of 1mM of ATT, these results are confirmed by the EIS techniques, indicating that the value of the charge transfer resistance increases with increasing of ATT concentrations, consequently the inhibitory efficiency increases and reaches a maximum value of 99% in the presence of 1mM of ATT. the influence of the immersion time shows that the corrosion inhibition of the brass 60Cu–40Zn improves with the increase of the immersion time and that the molecule adsorbs chemically and follows the Langmuir isotherm. SEM/EDS study confirms the presence of protective film on the Brass surface. Abstract : Electrochemistry; Materials chemistry; Physical chemistry, Alloy, ATT, Isotherm, Corrosion, Zero charge potential